MAGNETIC RESONANCE ANGIOGRAPHY AND BRAIN ISCHEMIA IN PATIENTS WITH ACUTE STROKE - KHALIL , SKF; AWAN , MW; ARSHAD , W; AMJAD , M; USMANI , NN (Biological and Clinical Sciences Research Journal, 2023)
This research investigates if Magnetic Resonance Angiography (MRA) can detect arterial disorders in patients with acute ischemic stroke with diffusion-positive infarction. The study was conducted at KRL Hospital in Islamabad from May 1, 2022, to September 30, 2022, after receiving ethical approval from the institutional review board. The study included participants between the ages of 45 and 60 of any gender who had symptoms of localized cerebral ischemia lasting less than 24 hours and were referred for MRI evaluation. Non-probability consecutive sampling was used to select participants. The Chi-square test compared MRA findings of vascular illness with MRI findings of brain parenchymal abnormalities. Out of 95 individuals, 89 (93.6%) showed a statistically significant correlation (p=0.001) between the arterial lesion and acute infarctions in the same region of the brain parenchyma on MRI. Only 6 (6.3%) of the 95 individuals showed a discrepancy between the location of the infarction on MRI and the results of the MRA. This study's findings suggest a significant positive association (95.34%) between MRA and MR diffusion restriction in acute ischemic strokes. This association supports the theory that an arterial vasculopathy is the underlying cause of the MR signal. However, in some cases, the discrepancy between MRA and infarction location might be due to an occlusive illness of an arterial branch that MRA did not detect.